Level of knowledge of the Menteng community RT 010 RW 009 Menteng Village regarding the use of mefenamic acid tablets as an NSAID analgesic - Azrizah Rahmadani; Amalina Fakhriah; Varda Arianti; Devi Maulina (Indonesian Journal of Health Science, 2026)
Mefenamic acid, a meclofenamate derivative, is a type of NSAID that inhibits the formation of the cyclooxygenase enzyme. This cyclooxygenase enzyme converts arachidonic acid into prostaglandins. Therefore, if this drug is given as a pain reliever to children or adolescents during their growth period, it will disrupt the longitudinal growth process of their bones. This study aims to evaluate the level of public knowledge in RT 010 RW 009, Menteng Village, Central Jakarta, regarding the use of mefenamic acid tablets as an NSAID analgesic. The method used is descriptive with a quantitative approach and involved 64 respondents selected based on inclusion criteria. The results show that the average level of public knowledge is in the sufficient category (63,20%). Respondents are predominantly in the 17–25 year age group with a vocational high school education level. Only 35.90% of respondents have received direct education from health workers. This finding emphasizes the importance of more intensive educational interventions from health institutions so that the public uses drugs appropriately and wisely.